Analysis and design of a computer-based enrollment information system for St. Mary's College of Meycauayan - Reyes, Joseph Bernard B. (Animo Repository, 2002)
This research designs, develops and assesses the proposed enrollment information system for St. Mary's College of Meycauayan, Bulacan. The study went through six phases: Enrollment Systems Analysis which consisted of the examination of the old enrollment system in order the find out its strengths, weaknesses and new requirements that might be needed in order to improve analysis of systems operations was done to specify the requirements and system scope for the new enrollment system cost-benefit analysis was formulated to determine the possibility of implementing the program Enrollment System Design in which the logical design for the new computer-based enrollment system was constructed based on the scope and requirements identified during the analysis phase Program coding in which the logical design is transformed into machine executable format using a suitable relational database programming language which is Microsoft FoxPro Testing in which the completed application software is first installed properly in the network and then the end-users were trained on how to use it Documentation in which all activities done in the study was captured and also specified diagrams were constructed in order to capture the old system and design the new system, and finally Evaluation in which the efficiency of the two system were compared based on the responses of students, middle administrators, personnel and database experts.